Rhododendron x 'Fashion' 'Fashion' Azalea: FPS508/FP508, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of the ‘Fashion’ azalea (Rhododendron x ‘Fashion’), including its botanical characteristics, planting guidelines, and care requirements. It highlights the plant’s suitability for various uses such as mass planting, container gardening, and attracting butterflies. The document also addresses potential pest issues and diseases, offering preventive measures and treatment options. Additionally, it mentions popular cultivars within the Gumpo series and their distinct flower colors. Original publication date October 1999.